Fast-food outlet availability and obesity: Considering variation by age and methodological diversity in 22, 889 Yorkshire Health Study participants. (February 2019) - Hobbs, M.; Griffiths, C.; Green, M.A.; Jordan, H.; Saunders, J.; Christensen, A.; McKenna, J.
Abstract: This study investigated if the relationship between residential fast-food outlet availability and obesity varied due to methodological diversity or by age. Cross-sectional data ( n  = 22, 889) from the Yorkshire Health Study, England were used. Obesity was defined using self-reported height and weight (BMI ≥ 30). Food outlets ("fast-food", "large supermarkets", and "convenience or other food retail outlets") were mapped using Ordnance Survey Points of Interest (PoI) database. Logistic regression was used for all analyses. Methodological diversity included adjustment for other food outlets as covariates and continuous count vs. quartile. The association between residential fast-food outlets and obesity was inconsistent and effects remained substantively the same when considering methodological diversity. This study contributes to evidence by proposing the use of a more comprehensive conceptual model adjusting for wider markers of the food environment. This study offers tentative evidence that the association between fast-food outlets and obesity varies by age.